2010
DOI: 10.1146/annurev.biochem.052208.114057
|View full text |Cite
|
Sign up to set email alerts
|

Amphipols, Nanodiscs, and Fluorinated Surfactants: Three Nonconventional Approaches to Studying Membrane Proteins in Aqueous Solutions

Abstract: Membrane proteins (MPs) are usually handled in aqueous solutions as protein/detergent complexes. Detergents, however, tend to be inactivating. This situation has prompted the design of alternative surfactants that can be substituted for detergents once target proteins have been extracted from biological membranes and that keep them soluble in aqueous buffers while stabilizing them. The present review focuses on three such systems: Amphipols (APols) are amphipathic polymers that adsorb onto the hydrophobic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
269
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(274 citation statements)
references
References 148 publications
(260 reference statements)
4
269
0
1
Order By: Relevance
“…To study Aβ oligomer formation in a membrane environment, we used detergent micelles, one of the most commonly used biomimetic membrane environments to examine the structure of membrane proteins and their complexes (18,19). However, detergent micelles have been reported to compete with the factors that stabilize protein-protein interactions (20). Accordingly, we envisioned that a large excess of free micelles could act as a "hydrophobic sink," in which Aβ subunits could disperse, leading to the disruption of Aβ oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…To study Aβ oligomer formation in a membrane environment, we used detergent micelles, one of the most commonly used biomimetic membrane environments to examine the structure of membrane proteins and their complexes (18,19). However, detergent micelles have been reported to compete with the factors that stabilize protein-protein interactions (20). Accordingly, we envisioned that a large excess of free micelles could act as a "hydrophobic sink," in which Aβ subunits could disperse, leading to the disruption of Aβ oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…However, detergents sometimes disrupt the native structure of arrestins. We examined arrestin-1 structure and stability using near-UV CD in the presence of different types of micelles, bicelles, and amphipols (25). Detergents and amphipols destabilized arrestin-1, whereas three different types of bicelles yielded CD spectra very similar to those observed in buffer only (Fig.…”
Section: Arrestin-1 Retains Native Structure In the Presence Of Anionmentioning
confidence: 92%
“…Furthermore, other alternatives exist, such as bicelles for crystallization [76]-commercial kits available (in the form of lipid-detergent mixture, typically DMPC with CHAPSO); fluorinated surfactants [46] and nanodiscs (a patch of the lipid bilayer encircled by membrane scaffolding proteins) [44] for protein stabilization. Fluorinated surfactants have not gained much attention so far, probably due to its nature-it has a hydrophobic tail with the incorporation of several fluorine atoms, rendering it lipophobic and preventing effective interactions with a membrane protein, typically causing aggregation of the latter.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…For the X-ray crystallography field, it has been shown that amphipols are compatible with lipidic cubic phases [42], thus currently amphipols can only be used for in meso crystallization [43], similarly to SMALPs. There are several other approaches developed (and being actively developed) for the stabilization of membrane proteins, including nanodiscs [44], calixarens [45], fluorinated surfactants [46] and others, but they are beyond the scope of this mini-review. (From top to bottom) the concentration of detergent is increased, until the protein is extracted in the form of the complex with detergent (and some residual lipids), surrounded by free detergent-lipid micelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation